Confirmatory factor analysis of the portuguese Depression Anxiety Stress Scales-21 Análisis factorial confirmatoria de la versión portuguesa de la Depression Anxiety Stress Scale-21 Análise fatorial confirmatória da versão portuguesa da Depression Anxiety Stress Scale-21 - João Luís Alves Apóstolo; Barry Allen Tanner; Cynthia Lee Arfken (Universidade de São Paulo, 2012)
To determine which of three published models best characterizes the factor structure of the Portuguese version of the Depression Anxiety Stress Scales-21 and to assess its validity and reliability. Confirmatory factor analysis of Depression Anxiety and Stress Scale-21 for 1,297 adult, primary care outpatients (66.7% female, Mage = 48.57 years) comparing 3 models. The relationship between the Depression Anxiety Stress Scales-21 and the Positive and Negative Affect Schedule was analyzed. The correlated 3-factor model fit the data best. The scale demonstrated good internal consistency, with alpha scores of the subscales ranging from 0.836 to 0.897. Correlation with the Positive and Negative Affect Schedule was positive and moderate with the negative affect scale; it was negative and limited with the positive affect. These findings support the correlated 3-factor structure. The test demonstrated adequate reliability and construct validity, which supports its use for screening in primary care settings with Portuguese speakers. El objetivo de este estudio fue determinar cual de los tres modelos publicados mejor caracteriza la estructura factorial de la versión portuguesa de la Depression Anxiety Stress Scale-21 (DASS-21) y evaluar su validez y confiabilidad. Se compararon los tres modelos a través de análisis factorial confirmatoria de la DASS-21, aplicada el 1.297 pacientes adultos, del servicio de atención básica (66,7% mujeres; edad Media=48,57 años). La relación entre la DASS-21 y la Positive and Negative Affect Schedule (PANAS) también fue analizada. El modelo de tres factores correlacionados se ajusta mejor a los datos. La escala presentó buena consistencia interna con valores alfa observados en las subescalas, variando de 0,836 a 0,897. La correlación con la PANAS fue positiva y comedida con la escala de afecto negativa, y negativa y limitada con la escala de afecto positivo. Esos resultados corroboran la estructura de tres factores. La prueba presentó confiabilidad adecuada y validez de constructo, dando soporte a su uso para rastrear pacientes portugueses en el servicio de atención básica. O objetivo deste estudo foi determinar qual dos três modelos publicados melhor caracteriza a estrutura fatorial da versão portuguesa da Depression Anxiety Stress Scale-21 (DASS-21) e avaliar sua validade e confiabilidade. Compararam-se os três modelos através de análise fatorial confirmatória da DASS-21, aplicada em 1.297 pacientes adultos, do serviço de atenção básica (66,7% mulheres; idade média=48,57 anos). A relação entre a DASS-21 e a Positive and Negative Affect Schedule (PANAS) também foi analisada. O modelo de três fatores correlacionados se ajusta melhor aos dados. A escala apresentou boa consistência interna com valores alfa observados nas subescalas, variando de 0,836 a 0,897. A correlação com a PANAS foi positiva e moderada com a escala de afeto negativa, e negativa e limitada com a escala de afeto positivo. Esses resultados corroboram a estrutura de três fatores. O teste apresentou confiabilidade adequada e validade de constructo, dando suporte ao seu uso para rastrear pacientes portugueses no serviço de atenção básica.